Reducing the energy demand of cellulosic ethanol through salt extractive distillation enabled by electrodialysis - Hussain, Mohammed A. M.; Pfromm, Peter H. (My University, 2013)
One of the main challenges when a biochemical conversion technique is employed to produce cellulosic ethanol is the low concentration of ethanol in the fermentation broth, which increases the energy demand for recovering and purifying ethanol to fuel grade. In this study, two design cases implementing salt extractive distillation – with salt recovery enabled by a novel scheme of electrodialysis and spray drying – along with heat integrated distillation techniques of double-effect distillation and direct vapor recompression are investigated through process simulation with Aspen Plus® 2006.5 for reducing the thermal energy demand. Conventional distillation along with molecular sieve based dehydration is considered as the base case. Salt extractive distillation along with direct vapor recompression is found to be the most economical ethanol recovery approach for cellulosic ethanol with a thermal energy demand of 7.1 MJ/L (natural gas energy equivalents, higher heating value), which corresponds to a thermal energy savings of 23% and cost savings of 12% relative to the base case separation train thermal energy demand and total annual cost.
Keywords: Ethanol; Distillation; Salt extractive; Cellulosic; Electrodialysis